Conceptualising horizontal politics - Harding, Eloise Mary (2012)
This project investigates the likelihood of a distinctive ideology emerging from what are known as ‘horizontal’ political movements – those which, in brief, aim to operate non-hierarchically guided by principles such as affinity – and furthermore to identify the potential components of such an ideology. The methodology is broadly based on that developed by Freeden, namely an analysis of the conceptual morphology of the ideas put out by horizontal movements. The sources used derive largely from the output of the movements themselves in various forms. I conclude that horizontal politics does have a recognisable ideological configuration, and that this is distinctive from other related ideologies such as anarchism.